Trends and Patient Characteristics Associated with Tobacco Pharmacotherapy Dispensed in the Veterans Health Administration. Issue 10 (9th October 2017) - Ignacio, Rosalinda V; Barnett, Paul G; Kim, Hyungjin Myra; Geraci, Mark C; Essenmacher, Carol A; Hall, Stephanie V; Chow, Adam; Pfeiffer, Paul N; Sherman, Scott E; Bohnert, Kipling M; Zivin, Kara; Duffy, Sonia A
Abstract: Introduction: There is evidence suggesting that certain subgroups of people who use tobacco do not receive tobacco pharmacology as consistently as others. Methods: This retrospective, cohort study examined the trend in the use of cessation pharmacotherapy from 2004 to 2013 using Veterans Health Administration (VHA) administrative data. Among Veterans who used tobacco in the fiscal year (FY) 2011 and had not received pharmacotherapy in the prior year, multivariable Cox regression was used to assess the independent associations between patient clinical and demographic characteristics and pharmacotherapy initiation in the 6-months follow-up period. Results: Smoking cessation pharmacotherapy in the VHA increased from 13.8% in 2004 to 25.6% in 2013. In 2011, Veterans ( N = 838309) who were more likely to newly receive pharmacotherapy included those with psychiatric disorders (depression, bipolar disorder, non-alcohol substance use disorder, other anxiety, and post-traumatic stress disorder), chronic pulmonary disease, peripheral vascular disorders, and younger Veterans (adjusted rate ratios (ARRs) ranged from 1.03 to 1.92, all p < .001). Veterans less likely to receive pharmacotherapy were those with schizophrenia or other psychosis, males, Hispanics, and those with a medical condition (uncomplicated diabetes, uncomplicated hypertension, fluid and electrolyte disorders, cardiac arrhythmia, valvular disease, hypothyroidism, acquired immunodeficiency syndrome/human immunodeficiency virus, deficiency anemia, renal failure, paralysis, coagulopathy, metastatic cancer, and other neurological disorders) (ARRs ranged from 0.74 to 0.93, all p < .001). Conclusions: Although VHA cessation pharmacotherapy use nearly doubled from 13.8% in 2004 to 25.6% in 2013, reaching undertreated subgroups, especially those with medical comorbidities, may improve cessation outcomes. Implications: Despite evidence that demographics influence the use of pharmacotherapy in smoking cessation, there is limited and contradictory information regarding how psychiatric and chronic medical illnesses affect pharmacotherapy use. Administrative data were used to determine trends and patient characteristics of those receiving pharmacotherapy to aid in smoking cessation in the Veterans Health Administration. From 2004 to 2013, pharmacotherapy use increased from 13.8% to 25.6% of current smokers. Factors associated with increased pharmacotherapy initiation were psychiatric disorders, chronic pulmonary disease, peripheral vascular disorders, and younger age. Veterans with schizophrenia or other psychosis, males, Hispanics, and most medical conditions were less likely to receive pharmacotherapy.